Recurrence of chest wall hydatid cyst disease involving the thoracic spine in an Australian patient. (August 2016) - Mon, Su Thet; Li, Yingda; Shepherd, Sarah; Daniel, Santosh; Poonnoose, Santosh; McDonald, Matthew
Highlights: Surgical intervention is required in patients with spinal cord compression secondary to spinal hydatid disease. We report on staged and minimally invasive surgery to minimise wound related complications. It is important to continue medical treatment in partially resected cases and long term follow up is essential. Abstract: Hydatid disease involving the spine is a relatively uncommon occurrence. The cestode Echinococcus granulosus is the primary pathogen associated with hydatid disease and most patients present with signs and symptoms of spinal cord compression depending on the location of the spinal involvement. We present a rare case of recurrent hydatid disease with extensive hemithorax involvement, including the thoracic spine, associated with spinal cord compression. This case highlights the role of staged and minimally invasive spine surgery in spinal hydatid disease with spinal cord compression, the importance of ongoing medical treatment and long term follow-up.